2019
DOI: 10.15666/aeer/1701_951968
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic and Conventional Farming Practices on Soil Quality: A Global Review

Abstract: As world population grows, the demand for food production increases ultimately creating a huge pressure on our shrinking natural resources. With this increased demand for food researches have realized that conventional farming would neither be able to increase productivity nor would be able to improve the soil quality and there is a need for an alternative farming practice to conserve our environment while sustaining the natural resources. Among the alternative practices, organic farming, which is very popular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
(72 reference statements)
0
9
0
1
Order By: Relevance
“…In recent years, the application of organic fertilizers for soil property has been greatly emphasized [ 8 , 9 ]. Some studies have shown that the application of organic fertilizers could significantly enhance soil quality in terms of soil structure, physicochemical properties and biological characteristics [ 10 , 11 ]. The combined application of organic and inorganic fertilizers could mediate organic carbon (C) sequestration, as well as elevate the nitrogen (N) and phosphorus (P) balance in soil environments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of organic fertilizers for soil property has been greatly emphasized [ 8 , 9 ]. Some studies have shown that the application of organic fertilizers could significantly enhance soil quality in terms of soil structure, physicochemical properties and biological characteristics [ 10 , 11 ]. The combined application of organic and inorganic fertilizers could mediate organic carbon (C) sequestration, as well as elevate the nitrogen (N) and phosphorus (P) balance in soil environments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ecological diagnoses of the consequences of agricultural practices are fundamental for deciphering which practices could be best for maintaining the soil fertility ecosystem service. Within this framework, an increasing number of published studies have focused on the consequences of different farming practices (i.e., conventional versus organic farming) on “soil quality” (i.e., soil physical properties, chemical properties, and biological properties) (for a review, see reference 5 ). However, little is known about the effects of the practices on the ecoevolutionary ecology of soil organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al (2019) reported that land‐use conversion from a crop field to a greenhouse vegetable field caused degradation of soil macropore structure, with macroporosity decreasing and pore morphology worsening. On the other hand, many studies have reported that organic farming can improve soil structural properties (Sheoran et al, 2019; Xu et al, 2018; Xu, Wang, Xie, et al, 2020). Our results showed that the macroporosity averaged 16.9% in OGV soils, more than twice as high as that in CGV soils.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that soil organic matter (SOM) exerts a positive effect on soil structure by promoting aggregate formation, decreasing bulk density and increasing porosity (Abdollahi, Schjonning, Elmholt, & Munkholm, 2014; Daynes, Field, Saleeba, Cole, & McGee, 2013; Franzluebbers, 2002; Riley, Pommeresche, Eltun, Hansen, & Korsaeth, 2008; Simansky, Juriga, Jonczak, Uzarowicz, & Stepien, 2019; Six, Paustian, Elliott, & Combrink, 2000; Xu, Wang, Tian, et al, 2020). However, comparisons of the effects of organic and conventional farming on soil structure have yielded inconsistent results (Sheoran et al, 2019; Shepherd, Harrison, & Webb, 2002). One mainstream view is that organic management improves soil structure compared with conventional farming (Fueki, Lipiec, Kus, Kotowska, & Nosalewicz, 2012; Papadopoulos et al, 2014; Pulleman, Jongmans, Marinissen, & Bouma, 2003; Schrama, de Haan, Kroonen, Verstegen, & van der Putten, 2018).…”
Section: Introductionmentioning
confidence: 99%